美国大学外语教学发展趋势及其对中文教育的启示 - Yanhao Wang (Universitas Negeri Malang, 2022)
本研究基于美国现代汉语协会所进行的一系列调查，分析了2002年至2016年期间美国大学外语课注册人数的发展趋势。研究指出，自上世纪五十年代以来，美国大学生对外语课的兴趣一直在波动上升，但总体增长率较低。2009年前后由于经济危机等因素，大学生对外语等人文学科的兴趣大幅度下降。中文课注册人数在2013年达到峰值，但随后锐减13%。本研究认为，为了推动中文教育在美国大学内的发展，教师应增强内容的实用性并鼓励学生进一步学习高级课程，国家也应该积极推动软实力建设，从而吸引更多的学生主动学习中文。 This research, based on reports published by Modern Language Association, analyzed enrollments in languages other than English in United States institutions of higher education from 2002 to 2016. Results show that American college students’ interest on foreign languages have been increasing unsteady since the 1950s, but the increasing rates kept low; and given the factors like the Great Depression since 2009, college students’ interests on foreign language and other disciplines of humanity have dropped abruptly. The enrollment of Chinese classes has reached its peak in 2013 but then experienced a 13% decrease. This study suggests, to promote Chinese education in the US, teachers should develop practical contents and encourage students to study advanced classes, and government of China should develop its soft power to attract more students to study Chinese.